EXPLORING THE PERSPECTIVE OF UPTQ STUDENTS: SURPASSING LIMITATIONS WITH DIGITAL APPLICATIONS FOR MEMORIZING THE QUR'AN - Thohir, Muhammad; Reditiya, Viola Eva (Sanata Dharma University Yogyakarta, 2024)
The presence of 4.0 technological advancements and the transformative forms of globalization have significantly impacted various aspects of life for modern society. Changes in culture, mindset, activities, politics, economics, and even the field of education nowadays tend to diminish the spiritual values of individuals and groups, particularly among students. The existence of the digital Qur'an also contributes to their interest in exploring the depth and convenience of memorizing the Qur'an. This research aims to describe the perspectives of students in memorizing the Qur'an with the help of a digital Qur'an application. The research method employed is qualitative research with a descriptive approach. The research subjects consisted of 68 individuals who joined a WhatsApp group. Data collection techniques involved observation, and in-depth interviews with the subjects, and the obtained data were analyzed descriptively. The study's findings recommend that the students' perspectives on the application for memorizing the Qur'an are highly positive, including a high interest in using the digital Qur'an, the beneficial features it provides, the impact of the digital Qur'an's existence, and the functions it encompasses.